Sosialisasi Kepelatihan Pencak Silat: Peran Workshop Kepelatihan IPSI Kabupaten Kuningan dalam Meningkatkan Prestasi - Yuzbaa Wulandari; Septian Williyanto; Hermawan Hermawa (Lembaga Pengembangan Kinerja Dosen, 2025)
Pencak silat is an Indonesian cultural heritage and tradition that is rich in philosophy, art, and sport. In Kuningan Regency, pencak silat is not only seen as a sport, but also as a means to build character and community discipline. Despite its great potential, the achievement of pencak silat in this area still faces challenges, such as the lack of quality training and understanding of effective techniques. To overcome this, the Indonesian Pencak Silat Association (IPSI) of Kuningan Regency held a coaching workshop aimed at improving and increasing the competence of coaches and achievements in the pencak silat sport in Kuningan Regency. This activity was held on December 28, 2024 at the Muhammadiyah University of Kuningan, which was attended by 60 participants from various pencak silat schools. Competent speakers provided material on the basics of coaching, competition regulations, competition techniques and strategies, and first aid for sports injuries. The results of this activity are expected to form coaches who are able to educate athletes to achieve achievements, especially in the West Java Provincial Sports Week (BK PORPROV) Qualification Round competition. Thus, the socialization of this coaching is expected to contribute to improving the achievements of pencak silat in Kuningan Regency.